Improving Mathematics Learning Outcomes Through the Media-Assisted TGT Model Fraction Card - Siti Rohimah; Muhammad Aunur Rofiq; Anna Mariyani (Jurnal Kiprah Pendidikan, 2026)
Mathematics has always been a frightening prospect for students, so mathematics learning outcomes are a constant concern for teachers and even educational institutions. This study aims to improve students' mathematics learning outcomes through the application of a cooperative learning model.Team Games Tournament (TGT)supported by the mediafraction card. This research is based on the low mathematics learning outcomes of fifth-grade students of SDN Balong, with an average score of 48.42 from the KKM of 70. This research is a Classroom Action Research (CAR) carried out in two cycles, each including planning, implementation, observation, and reflection. The research subjects were 19 fifth-grade students of SDN Balong in the 2024/2025 academic year. Data collection techniques included documentation, interviews, observations, and tests. Data validity was tested by triangulation of sources and methods. The results of the study indicate that the application of the TGT model assistedfraction cardcan improve teacher skills, student activity, and mathematics learning outcomes. This is evidenced by the learning outcomes achieved in cycle I, which reached 68.42% cognitive learning completion, increasing to 78.94% in cycle II. Student activity and teacher skills also experienced significant improvements. Thus, the TGT cooperative learning model is effective in improving the quality of mathematics learning